IMPLEMENTATION OF THE CREATION OF A POLICE RECORD CERTIFICATE (SKCK) BASED ON THE POLRI SUPER APP APPLICATION IN THE TULUNGAGUNG REGENCY AREA (INTERNATIONAL SEMINAR, 2024)
The increasingly high use of information technology in the modern era demands that the government increasingly develop e-government. By running e-government properly, public services will be able to continue to improve and increase their quality in serving the community. Evaluation is a tool to ensure that public services continue to run well according to their goals. This study aims to find out the evaluation of the service of making police record certificates based on the police super app application and explain some obstacles in its implementation in online SKCK services. Methods this study uses in this study is qualitative descriptive which obtains data using interview techniques.  The result of the research that the online SKCK service using the POLRI SUPER APP application is able to run well and can meet the demands of the community in order to provide convenience for all people in the regionTulungagung area, not to mention that there are several obstacles faced starting from not all regional police stations in Tulungagung can access this application, as well as obstacles from the application itself such as technical problems with server errors. Making people reluctant to try to use the application and reconsidering it for the creation of SKCK.